Penerapan Model Pembelajaran Discovery Learning Berbantuan Leaflet untuk Meningkatkan Hasil Belajar Kognitif Siswa Kelas VIII - Basir, Rian Sang; Rohmawati, Imaya (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2023)
This research aims to determine students' cognitive learning outcomes by applying the leaflet-assisted discovery learning model to human excretory system material. This research is Classroom Action Research (CAR) with a quantitative descriptive approach, carried out in two cycles, with one meeting held in each cycle. The population in this study were all students at SMP Negeri 1 Blitar with the sample taken being 37 class VIII students. Data collection techniques include tests and documentation. The results of the research show that there is an increase in cognitive learning outcomes with the application of the leaflet-assisted discovery learning model. This is proven by the students' cognitive learning results in cycle I of 64.86% and in cycle II of 100%. The conclusion that can be drawn is that the application of the leaflet-assisted discovery learning model can improve the cognitive learning outcomes of class VIII students at SMP Negeri 1 Blitar on the structure and function of the human excretory system.